STUDI PENGGUNAAN BAHAN ALAM PADA PEWARNA BATIK DI SANGGAR DUA PUTRI KELURAHAN JELMU KECAMATAN PELAYANGAN KOTA JAMBI - INDAH PERMATA SARI, Dr. Yahya, M.Pd., Drs. Erwin A, M.Sn. (Serupa The Journal of Art Education, 2017)
The purpose of this study are: (1) describe the process of processing of natural materials; (2) describe how the process; (3) describe the natural colors produced batik studio Two Women Sub Jelmu Pelayangan District of the city of Jambi. The method used is a qualitative approach with descriptive research. The research subject is the founder of the studio Two Women, owners and workers, cultural and natural color batik observers Jambi. Shaped research data written records, recordings, interviews, and documentation of natural batik production studio Two Women. Research findings that the processing of natural materials for dyeing batik must use fresh ingredients. Staining process must be soaked evenly so that the color obtained average. The color of mango leaves are yellowish-green skin is brown and wood jengkol bulian is brownish red.Keywords: material processing, dyeing process, the color